(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
This paper presents the main results of a sociopragmatic study of mitigation in the PRESEEA corpus of Santiago de Chile. The method of analysis follows the proposals of, among others, Cestero and Albelda (2012), Briz and Albelda (2013), Cestero y Rodríguez Alfano (2014) and Albelda et al. (2014), which allows to integrate the linguistic, pragmatic-discursive and social factors. From the examination of nine hours of recordings of the Chilean variety of Spanish, obtained from 18 semi-structured interviews, it is concluded that speakers produce 750 mitigated speech acts and a total of 1731 mitigating devices. It is also shown that the main function of mitigating devices in Chilean Spanish is self-protection, and that modus mitigation tends to be the most widely used type of mitigation, mainly through reasons and excuses. Finally, it is concluded that the greater variability occurs in relation to the age and level of education of participants.